2019
DOI: 10.21203/rs.2.17183/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rising Prevalence of Multiple Sclerosis in Saudi Arabia, a Descriptive Study

Abstract: Introduction In 2015, the first nationwide, multi-center MS registry was initiated in Saudi Arabia mainly with an objective to describe current epidemiology, disease patterns, and clinical characteristics of MS in Saudi Arabia. This article aimed to report initial findings of the registry and regional prevalence of MS. Method The registry included patients with confirmed MS diagnosis according to the 2010 McDonald Criteria. It aimed to identify and recruit all healthcare facilities treating MS patients in the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…Studies from around the globe have reported a female preponderance of MS. 26,27 The gender gradient in this study is confirmed from the Saudi registry of MS, which has established a 2:1 female:male ratio of MS in the country. 28 This difference could be explained by inherent differences in genetics and in physiological responses to other proposed risk factors, such as environmental and medical risk factors. It has also been proposed that the female preponderance of MS could be related to changes in environmental interactions rather than genetic factors.…”
Section: Methodsmentioning
confidence: 99%
“…Studies from around the globe have reported a female preponderance of MS. 26,27 The gender gradient in this study is confirmed from the Saudi registry of MS, which has established a 2:1 female:male ratio of MS in the country. 28 This difference could be explained by inherent differences in genetics and in physiological responses to other proposed risk factors, such as environmental and medical risk factors. It has also been proposed that the female preponderance of MS could be related to changes in environmental interactions rather than genetic factors.…”
Section: Methodsmentioning
confidence: 99%
“… 10 According to the 2013 MS Atlas, 11 Middle Eastern and North African countries are located in a low- to moderate-risk zone for MS; however, recent studies have reported increased prevalence in these countries especially among women. 12 16 This increased prevalence, not only imposes a huge burden on the healthcare systems, but also negatively affects the quality of life of impacted patients and their families. Thus, it is important to study the multiple domains and underlying risk factors that are associated with the rising prevalence of MS, and that in turn could benefit the healthcare planning and policymaking.…”
Section: Introductionmentioning
confidence: 99%
“…The Gulf area was historically considered to have a low MS prevailing, but in recent years, data indicates a dramatic increase of prevalence rates of 31-55 MS per 100,0000 in the number of MS cases in general in the region, including Saudi Arabia [14]. No national or regional registers in the country are still available to explain the actual disease burden and obtain precise estimates [108]. According to few reports, the Gulf region's increased prevalence may be attributed to lifestyle changes, vitamin D deficiencies and parental consanguinity [13,109].…”
Section: Genetic Polymorphisms Studies and Ms In The Saudi Arabia Popmentioning
confidence: 99%